Evaluasi Implementasi Fasilitas Intelligent Transport System di Kota Surabaya - Fazrian, Sitti Adiyaksa; Hermana, Joni (Syntax Corporation, 2025)
Due to the rapid growth of motorized vehicles, Surabaya City faces significant challenges related to traffic congestion and greenhouse gas (GHG) emissions. This growth harms air quality and worsens climate change. Therefore, finding practical solutions to reduce GHG emissions in the transportation sector is important. One potential solution is the implementation of an Intelligent Transport System (ITS), which can improve traffic management and transportation efficiency. This study aims to evaluate the effectiveness of ITS implementation in reducing GHG emissions in Surabaya City. The research methods used include primary data collection through interviews and questionnaires and secondary data obtained from official reports and the implemented ITS system. The analysis was carried out by considering three main aspects: technical, environmental, and institutional, using the CLIMACT Prio method to determine the priority of appropriate mitigation actions. The study's results indicate that implementing an Intelligent Transport System (ITS) in Surabaya City can reduce greenhouse gas (GHG) emissions through several main approaches. ITS optimizes traffic management by reducing congestion and idle time, reducing emissions. In addition, ITS increases the use of public transportation and supports the integration of environmentally friendly vehicles, such as electric vehicles, which reduce dependence on fossil fuels.